Fiji : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1995)
This paper reviews economic developments in Fiji during 1990-95. The reorientation of policies, although incomplete, led to stronger growth of nontraditional exports and non-sugar manufacturing, and to a pickup in GDP growth to an average of 4.1 percent between 1988 and 1993. Fiscal deficits declined in the early 1990s, although often larger than budgeted, and the external current account progressively turned into a surplus position. Despite the actions undertaken, however, private investment did not recover from its slump in the late 1980s impeding the economy from fully exploiting its growth potential.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet